The Effects of Distributive and Interactional Justice on The Dysfunctional Behavior of Millennials - Heru Kurnianto Tjahjono; Majang Palupi; Fauziyah Fauziyah (Equity: Jurnal Ekonomi, 2026)
Experimental studies related to the effects of perceived justice on dysfunctional behavior have not been widely conducted. Studies related to fair treatment within organizations and its impact on dysfunctional aspects within organizations are relatively rare, especially considering the specific impact of organizational justice configuration patterns on dysfunctional behavior. The purpose of this study is to specifically examine the effects of distributive justice (DJ) and interactional justice (IJ) in various contexts and their impact on dysfunctional behavior. The study uses millennial subjects to gain an understanding of the attitudes and behaviors of this generation in responding to distributive and interactional justice. An experimental study was conducted to obtain artificial situations in four justice situations, namely high DJ - high IJ, high DJ – low IJ, low DJ – high IJ, and low DJ - low IJ. The results show that the interaction of distributive justice and interactional justice has a different impact on dysfunctional behavior, and millennials tend to be more concerned about welfare than interactional aspects.